Exploration of Iron- and α-Ketoglutarate-Dependent Dioxygenases as Practical Biocatalysts in Natural Product Synthesis - Renata, Hans (Synlett, 2020)
Catalytic C–H oxidation is a powerful transformation with enormous promise to streamline access to complex molecules. In recent years, biocatalytic C–H oxidation strategies have received tremendous attention due to their potential to address unmet regio- and stereoselectivity challenges that are often encountered with the use of small-molecule-based catalysts. This Account provides an overview of recent contributions from our laboratory in this area, specifically in the use of iron- and α-ketoglutarate-dependent dioxygenases in chemoenzymatic syntheses of complex natural products.1 Introduction2 Overview of Natural Oxygenases3 C5 Hydroxylation of Aliphatic Amino Acids4 Chemoenzymatic Synthesis of Tambromycin5 Chemoenzymatic Synthesis of Cepafungin I and Related Analogues6 Chemoenzymatic Synthesis of GE81112 B1 and Related Analogues7 Conclusion and Future Direction
Keywords: C–H hydroxylation; natural products; biocatalysis; total synthesis; amino acids; oxygenases